Le lacanisme en Espagne - Anne-Cécile Druet (Casa de Velázquez, 2008)
This article analyses the characteristics of the beginnings of the Lacanian movement in Spanish psychoanalysis, through the prism of the theory of «cultural transfer». In the late 1970s and  early 1980s Spain saw the emergence of a Lacanian school of psychoanalysis around exiled Argentinian analysts, and above all Oscar Masotta, who had been the chief proponent of Lacanism in Argentina. The birth of this school, its institutionalisation and the initial grounding of future Spanish analysts hence share a triangular history in which the way that Lacan’s theories were received in one country, Argentina, in turn influenced the way these were introduced into another country, Spain. After first presenting the context of Freudian Spain in 1975, the author stresses the changes that took place in the field of psychoanalysis following the arrival of Oscar Masotta and analyses the ways in which the Lacanian movement grew up in Spain, from the perspective of the cultural transfer that took place then.